Inverse Association of General Joint Hypermobility With Hand and Knee Osteoarthritis and Serum Cartilage Oligomeric Matrix Protein Levels - Chen, Hsiang-Cheng (2008)
OBJECTIVE: Extensive joint hypermobility, lower serum cartilage oligomeric matrix protein (COMP), and early-onset osteoarthritis (OA) are phenotypes of inherited pseudoachondroplasia (PSACH) and multiple epiphyseal dysplasia (MED). However, few studies have evaluated the association between articular hypermobility and primary OA. Therefore, we evaluated this association and tested the hypothesis that COMP level is associated with hypermobility in OA and non-OA individuals. METHODS: Two separate cohorts were available for analysis, the extended CARRIAGE family and a subset of the GOGO sib pair cohort. In the CARRIAGE family, we performed hand and knee examinations, hypermobility evaluations (Beighton criteria), and obtained sera for COMP and hyaluronan (HA). COMP and HA, extensive joint radiographic and hypermobility data were also available for the GOGO cohort. RESULTS: The prevalence of hypermobility was 13% in the CARRIAGE and (5%) in the GOGO cohort. In the CARRIAGE family, hypermobility was associated with a significantly lower prevalence of hand (especially proximal interphalangeal joint) and knee OA, and lower mean serum COMP in both the total cohort and non-hand OA subgroups. These results were further validated in the GOGO subsets without radiographic OA where hypermobility was also associated with a significantly lower mean serum COMP (p<0.01). Serum HA did not differ on the basis of hypermobility in either cohort. CONCLUSIONS: We report an inverse relationship of hypermobility, hand and knee OA, and show that hypermobility is associated with lower serum COMP levels. Genetic variations of the COMP gene may account for some subgroups of benign joint hypermobility.